2019
DOI: 10.29333/iji.2019.12134a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blended Learning on Student's Learning Achievement and Science Process Skills in Plant Tissue Culture Course

Abstract: The purpose of this research was to know the effect of blended learning strategy on learning achievement and science process skills of students in plant tissue culture course in the Universitas Negeri Medan. The research method was quasi experiment. The population of this study was all semester VIII students of biology education program. The study sample consists of two classes, namely: class A known as control class who were taught by conventional learning strategy and class C known as experiment class who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
0
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 19 publications
9
83
0
14
Order By: Relevance
“…In the literature, studies have reported that blended learning has the potential to contribute to various skills including twenty-first century skills. Research has reported that the blended learning model positively contributed to students’ problem-solving skills (Suprabha and Subramonian 2019 ), science process skills (Harahap et al 2019 ), professional development skills (Yeh et al 2011 ), transfer of learning and knowledge transformation skills (Demirer and Sahin 2013 ; Jou et al 2016 ), self-directed learning skills (Akgunduz and Akinoglu 2016 ), visual literacy skills (Huilcapi-Collantes et al 2020 ), language skills (Hossein and Gwo-Jen 2020 ; Mingyong 2015 ), collaborative learning skills (Liu and Shi 2016 ), critical thinking skills (Jou et al 2016 ), and self-determination for learning (Joo et al 2013 ). In addition, Yeh et al ( 2011 ) concluded that the blended learning model developed the professional knowledge and personal teaching efficacy of preservice teachers.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies have reported that blended learning has the potential to contribute to various skills including twenty-first century skills. Research has reported that the blended learning model positively contributed to students’ problem-solving skills (Suprabha and Subramonian 2019 ), science process skills (Harahap et al 2019 ), professional development skills (Yeh et al 2011 ), transfer of learning and knowledge transformation skills (Demirer and Sahin 2013 ; Jou et al 2016 ), self-directed learning skills (Akgunduz and Akinoglu 2016 ), visual literacy skills (Huilcapi-Collantes et al 2020 ), language skills (Hossein and Gwo-Jen 2020 ; Mingyong 2015 ), collaborative learning skills (Liu and Shi 2016 ), critical thinking skills (Jou et al 2016 ), and self-determination for learning (Joo et al 2013 ). In addition, Yeh et al ( 2011 ) concluded that the blended learning model developed the professional knowledge and personal teaching efficacy of preservice teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus is to provide an interesting and motivating learning environment that can increase the effectiveness of their learning. (Chin et al, 2018;Harahap & Manurung, 2019;Tsai, Lin, & Lin, 2017). The blended learning model has several types, including Station Rotation, Lab Rotation, Individual Rotation, Flipped Classroom, Flec, A La Carte, and Virtual Enriched (Lopes & Soares, 2018;Staker & Horn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Blended Learning also combines traditional learning which is done by telling instruction subject as face to face with learning media based on digital technology. Blended learninggives more space for learning environment efficientlywhich is combining online learning, tradisional learning, learning contents and flexibility learning model,then students can be motivated to increase learning process effectivity [3]- [7]. Face to Face Driver, Flip, Rotation, Online Lab, Flex, dan Online Driver are some types of blended learning model [8].…”
Section: Introductionmentioning
confidence: 99%